Mitochondrial dysfunction of Astrocyte induces cell activation under high salt condition - Yuemin Qiu; Gengxin Lu; Shifeng Zhang; Li Minping; Xu Xue; Wu Junyu; Zhihui Zheng; Weiwei Qi; Junjie Guo; Dongxiao Zhou; Haiwei Huang; Zhezhi Deng (Heliyon)
Excess dietary sodium can accumulate in brain and adversely affect human health. We have confirmed in previous studies that high salt can induce activation of astrocyte manifested by the secretion of various inflammatory factors. In order to further explore the effect of high salt on the internal cell metabolism of astrocytes, RNA sequencing was performed on astrocytes under high salt environment, which indicated the oxidative phosphorylation and glycolysis pathways of astrocytes were downregulated. Next, we found that high salt concentrations elicited astrocyte mitochondrial morphology change, as evidenced by swelling from a short rod to a round shape through a High Intelligent and Sensitive Structured Illumination Microscope (HIS-SIM). Furthermore, we found that high salt concentrations reduced astrocyte mitochondrial oxygen consumption and membrane potential. Treatment with 18-kDa translocator protein (TSPO) ligands FGIN-1-27 improved mitochondrial networks and reversed astrocyte activation under high-salt circumstances. Our study shows that high salt can directly disrupt astrocytic mitochondrial homeostasis and function. Targeting translocator protein signaling may have therapeutic potential against high-salt neurotoxicity.